(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay analyzes the recent decision January 21st, 2022, n. 1842 with which the Court of Cassation (I Sez.) proposes a revision of the scope of application of the limit of public order constituted by the prohibition of surrogacy. In particular, the intervention focuses on the identification of the legal assets protected by the criminal law, focusing on the dignity of the pregnant woman and how this can be protected even in legal systems where surrogacy is allowed, provided that certain minimum elements are respected.